2015
DOI: 10.5194/osd-12-2473-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indian Ocean Dipole modulated wave climate of eastern Arabian Sea

Abstract: Abstract. Intrinsic modes of variability have a significant role in driving climatic oscillations in the ocean. In this paper, we investigate the influence of inter-annual variability, the Indian Ocean Dipole (IOD), on the wave climate of the eastern Arabian Sea (AS). Using measured, modeled and reanalysis wave data and reanalysis wind data, we show that the IOD plays a major role in the variability of wave climate of the study region due to the IOD induced changes in equatorial sea surface temperature and sea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…During negative IOD years surface winds are strong north to north-westerlies with wind vectors converging strongly over the TIP area. A study by Anoop et al (2016) had also found that the winds are north easterlies over the central west coast of India during the positive IOD years and as such they do not support coastal upwelling when compared to the negative IOD years. Lower SSTs and strong cyclonic surface winds can induce stronger than normal upwelling along CEAS as also evidenced by the higher than normal Chl_a concentrations during 1998 and 2010 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During negative IOD years surface winds are strong north to north-westerlies with wind vectors converging strongly over the TIP area. A study by Anoop et al (2016) had also found that the winds are north easterlies over the central west coast of India during the positive IOD years and as such they do not support coastal upwelling when compared to the negative IOD years. Lower SSTs and strong cyclonic surface winds can induce stronger than normal upwelling along CEAS as also evidenced by the higher than normal Chl_a concentrations during 1998 and 2010 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…June-August is considered to be the developing phase of IOD whereas September-November is considered to be the mature phase (eg: Hong, 2008). Anoop et al, (2016) found that in the month of October different phased IOD events have significant influence on the wave climate off the central west coast of India compared to the northern and southern parts. The differential warming of the tropical oceans which can either increase or decrease the zonal temperature gradient can have severe implications on the general oceanic-atmospheric circulation pattern (eg: Swapna et al, 2014) and accordingly marine biological activity (Roxy et al, 2016).…”
mentioning
confidence: 99%
“…Impact of ENSO and PDO on surface waves were investigated by Kumar et al (). However, across the North Indian Ocean, there have been limited studies on the impacts of regional atmospheric circulation patterns (Indian Ocean Dipole) on the wave climate (Anoop et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It highlights the role of IOD in wave climate variability induced by changes in the equatorial sea‐surface temperature and SLP. The changes in wind field over the Arabian Sea caused by the influence of IOD in turn can affect the generation or dissipation of wave field and cause decreased/increased northwest short period waves during positive/negative IOD phases (Anoop et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Anoop et al . () linked the waves in the North IO (NIO) with IOD. Their study revealed an intrinsic mode of variability that has a significant role in driving climate oscillations in the ocean.…”
Section: Introductionmentioning
confidence: 99%